2011
DOI: 10.1007/s00394-011-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extra virgin olive oil diet enriched with hydroxytyrosol in a chronic DSS colitis model

Abstract: EVOO diets exerted a noteworthy beneficial effect in chronic DSS-induced colitis by cytokine modulation and COX-2 and iNOS reduction via downregulation of p38 MAPK. In addition to the beneficial effect by EVOO, supplementation of the diet with hydroxytyrosol may improve chronic colitis through iNOS downregulation plus its antioxidant capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
2
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 40 publications
5
99
2
5
Order By: Relevance
“…In contrast, in a DSS-induced chronic colitis in mice, Sánchez-Fidalgo et al[13] reported that a diet containing 10% of EVOO enriched with a polyphenol extract reduced histopathological colitis scores and inflammatory markers. They also demonstrated that dietary EVOO and EVOO enriched with hydroxytyrosol reduced the severity of chronic colonic damage induced by an acute exposure to DSS [12]. Similarly, Takashima et al[30] reported that a 5% olive oil-rich diet attenuated inflammation in DSS-induced colitis in rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, in a DSS-induced chronic colitis in mice, Sánchez-Fidalgo et al[13] reported that a diet containing 10% of EVOO enriched with a polyphenol extract reduced histopathological colitis scores and inflammatory markers. They also demonstrated that dietary EVOO and EVOO enriched with hydroxytyrosol reduced the severity of chronic colonic damage induced by an acute exposure to DSS [12]. Similarly, Takashima et al[30] reported that a 5% olive oil-rich diet attenuated inflammation in DSS-induced colitis in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Although multiple sources of evidence support the anti-inflammatory effect of olive oil and its phenolic compounds [3], their beneficial effects in inflammatory bowel disease (IBD) have been almost exclusively studied in animal models of chemically induced colitis and involved the reduction of COX-2 and iNOS expression [12, 13]. However, such animal models do not accurately reflect the human disease pathogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…This preparation, called HT-20, significantly inhibited the acute inflammation and lowered tissue IL-1 and TNF levels. More recently, Sánchez-Fidalgo et al [131] reported that HTyr -enriched extra-VOO attenuated chronic dextran sulfate sodium (DSS)-induced colitis in mice and decreased COX-2, iNOS via downregulation of p38MAPK. Accordingly, Giner et al [125] found that oleuropein ameliorates acute DSS-colitis in mice while reducing TNF , IL-1 and IL-6 production, iNOS, COX-2 and MMP-9 expression, and NF-kB activation in colon tissue.…”
Section: In Vivo Htyr-mediated Anti-inflammatory Activity and Cancermentioning
confidence: 99%
“…The level of MPO activity is directly related to the neutrophil concentration in the inflamed tissue Therefore, measuring MPO activity is considered as a quantitative and sensitive assay for acute intestinal inflammation (44). Many studies showed that herbs and their main components such as phenols and polyphenols decreased MPO level and improved inflammation in the colonic tissue of ulcerative colitis animals (45)(46)(47). In this study, a significant reduction was detected in neutrophil infiltration in colonic mucus and MPO activity of animal subjects with colitis treated with M. officinal.…”
Section: Discussionmentioning
confidence: 99%